2021
DOI: 10.3390/cancers13205061
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Landscape of Immunotherapy for Primary Central Nervous System Lymphoma

Abstract: Primary central nervous system lymphoma (PCNSL) is, mainly, a diffuse large B-cell lymphoma (DLBCL) with a non-germinal center B-cell (non-GCB) origin. It is associated with a poor prognosis and an unmet medical need. Immunotherapy has emerged as one of the most promising areas of research and is now part of the standard treatment for many solid and hematologic tumors. This new class of therapy generated great enthusiasm for the treatment of relapsed/refractory PCNSL. Here, we discuss the challenges of immunot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…96,97 The current status of immunotherapy in PCNSL is nicely reviewed here. 98 Responses to chemotherapy are poor in the relapsed setting and toxicities are high, indicating that such therapies should only be offered after careful discussion of goals of care and consideration of palliative care or hospice therapy alone. 87…”
Section: Surveillance Postremission Therapymentioning
confidence: 99%
“…96,97 The current status of immunotherapy in PCNSL is nicely reviewed here. 98 Responses to chemotherapy are poor in the relapsed setting and toxicities are high, indicating that such therapies should only be offered after careful discussion of goals of care and consideration of palliative care or hospice therapy alone. 87…”
Section: Surveillance Postremission Therapymentioning
confidence: 99%
“…Indeed, the histogenetic origin of the tumor cells is still debatable, as the CNS is known to not harbor lymphatic vessels or lymph nodes [13]. Interestingly, recent studies showed the presence of lymphatic vessels, parallel to dural venous sinuses, in the meninges of mammals [14]. Moreover, there is growing evidence about the existence of a ''glymphatic system,'' which uses periarterial spaces and constantly clears interstitial fluid into the cerebrospinal fluid through the brain parenchyma [14,15].…”
Section: Pathophysiology and Histogenetic Origin Of Primary Central N...mentioning
confidence: 99%
“…Pathologically, more than 95% of PCNSL cases are diffuse large B cell lymphoma [ 120 , 121 ]. Gene expression analysis confirmed that non-germinal center B-cell (GCB) is the most common phenotype in PCNSL patients [ 121 124 ]. PCNSL cases often carry mutations that lead to activation of the NF-κB pathway, such as activating mutations in MYD88, CDKN2A, TNFAIP3 and CD79 B , suggesting that activation of the NF-κB pathway is a key driver of lymphangiogenesis in PCNSL[ 123 , 125 136 ].…”
Section: Primary Central Nervous System Lymphomamentioning
confidence: 99%